COL4A1 gene mutations and perinatal intracranial hemorrhage in neonates: case reports and literature review - Bersani, Iliana; Ronci, Sara; Savarese, Immacolata; Piersigilli, Fiammetta; Micalizzi, Alessia; Maddaloni, Chiara; Dotta, Andrea; Braguglia, Annabella; Longo, Daniela; Campi, Francesca (Frontiers in Pediatrics, 2024)
Intracranial hemorrhage may represent a complication of the perinatal period that affects neonatal morbidity and mortality. Very poor data exist about a possible association between mutations of the type IV collagen a1 chain (COL4A1) gene and the development of intracranial hemorrhage, and only sporadic reports focus on intracerebral bleedings already developing in utero or in the neonatal period in infants with such a mutation. This study presents a case series of term neonates affected by intracranial hemorrhage, with no apparent risk factors for the development of this condition, who were carriers of COL4A1 gene variants. This study also provides a review of the most recent scientific literature on this topic, specifically focusing on the available scientific data dealing with the perinatal period.